Uji Kualitas Tanah Dan Arahan Pengelolaannya Pada Budidaya Padi Sawah Di Subak Jatiluwih, Penebel, Tabanan - PUTU EKA CAHYADEWI; I WAYAN DIARA; I DEWA MADE ARTHAGAMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
Soil Quality Test and Its Management Directives on Rice Cultivation in Subak Jatiluwih, Penebel, TabananThe purpose of the study was to determine the quality of the soil and the management directives for rice cultivation at the research site. This study used survey methods and soil tests in the Laboratory of Soil Science and Environment. It consists of several stages of survey management of the system by the farmers, the analysis of the soil followed by the determination of the quality of the soil and the direction of management. The result showed that land in the research site has good and medium soil quality. The location which has good qualities was in sample IV, the medium quality was in sample I, II, III, V and VI. The management directives which were recommended for the medium soil quality were the improvement of soil management system. The processor which was recommended in this research was using tractors and livestock. The recommended types of plants were the local and new rice varieties. The recommended straw management was embedded back into the ground. The use of fertilizer which was recommended was the use of urea and SP-36 fertilizers. The recommended land use intensity cropping twice a year.